Population, resources, and conflict - Langwith, Jacqueline (Confronting global warming, 2011)
Explores in detail the range of current and impending challenges the planet faces as a result of global warming. Examines these issues from a variety of expert perspectives, highlights key future challenges, and addresses the pros and cons of potential solutions. This volume focuses on population, resources, and conflict.